A Phenomenological Psychology Study of University Teachers' Lived Experience of Being Pedagogical in Neoliberalism - Li, Yulong; Liu, Xiaojing (Frontiers in Psychology, 2022)
Against a background of promoting the industrialisation of higher education in Macau due to Covid-19’s damage to the territory’s major industry – gambling, the present study adopted phenomenological psychology to explore teachers’ lived experience of being pedagogical in a university with a neoliberal vision and mission. Using a general structure, the findings revealed that teachers encountered challenges being pedagogical. These challenges emerged not only due to the university’s corporate management, but more importantly because of a shift in perceptions – where students became like customers and teachers became self-interested – which made pedagogical relationships difficult to establish. Furthermore, teachers were found to develop negative emotions when their pedagogical actions or intentions conflicted with neoliberalism. The findings suggest that pedagogy in higher education is being challenged and transformed.